Development of voice onset time in standard-Greek and Cypriot-Greek-speaking preschoolers - Okalidou, Areti; Petinou, Kakia; Theodorou, Eleni; Karasimou, Eleni (My University, 2010)
The current investigation examined the development of voice onset time (VOT) in Standard-Greek (SG) and Cypriot-Greek (CG)-speaking children at age levels 2;0-2;5, 2;6-2;11, 3;0-3;5, and 3;6-4;0 years. SG presents with a two-way voicing contrast (voiced and voiceless unaspirated stops) whereas CG is a three-way contrast dialect containing voiceless unaspirated, voiceless aspirated, and pre-voiced stops. A cross-sectional design was used. The main goals were: (1) to determine the age at which Greek and Cypriot Greek children acquire voicing contrasts, and (2) to examine the mechanism used during the process of acquisition. Stimuli included pseudo words in minimal pair contrasts differing in stop voicing (e.g. ['gaga] vs ['kaka]). Children were taught the target words using fast mapping procedures. Each member within a word pair referred to an unfamiliar object. Audio-recorded samples were analysed from wide-band spectrograms. Results indicated a greater overall variation of voicing patterns for children than adults, in both Greek and Cypriot VOT contrasts. Greek children acquired consistent pre-voicing and short lag aspiration patterns very early on, achieving adult values for VOT contrasts for alveolar and for velar places of articulation as early as 2;0-2;5 years old. On the contrary, a developmental lag in the acquisition of voicing contrasts was noted for Cypriot children as compared to the Greek counterparts. Accounts about the developmental differences among Greek and Cypriot children with respect to the adult VOT contrasts are discussed.
Keywords: Acoustic analysis; Cypriot Greek; Phonological acquisition; Standard Greek; Voice onset time